2006
DOI: 10.1124/jpet.106.111724
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-Specific Factors Modulate Epidermal CYP1–4 Gene Expression in Human Skin in Response to Retinoic Acid and Classic Aryl Hydrocarbon Receptor Ligands

Abstract: Human epidermal keratinocytes express subsets of cytochromes P450 (P450) (CYP gene products) that are strongly up-regulated, not regulated, or down-regulated by differentiation-specific factors. We investigated how drug exposure affects epidermal expression of CYP1-4 genes, which encode many drug-metabolizing P450s. Real-time polymerase chain reaction (PCR) assays measured CYP1-4 mRNA levels in epidermal keratinocytes differentiated in vitro in the presence of drug or vehicle for 6 days. We confirmed the spino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…However, only a few studies have focused on the metabolism and biology of PAHs in NHEKs [18][19][20]. The present study demonstrated the nuclear translocation of AhR from cytoplasm after BaP [ ( ) T D $ F I G ] Fig.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, only a few studies have focused on the metabolism and biology of PAHs in NHEKs [18][19][20]. The present study demonstrated the nuclear translocation of AhR from cytoplasm after BaP [ ( ) T D $ F I G ] Fig.…”
Section: Discussionmentioning
confidence: 64%
“…*p < 0.05 compared to DMSO-treatment (control). ligand such as resveratrol and curcumin inhibit NF-kb activation although they induce translocation of AhR into nuclei [18,[43][44][45]. These findings suggest that further studies are required to elucidate the precise mechanism of RelB/AhR-mediated IL-8 production.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…We showed in previous studies that characterization of the CYP expression pattern in the skin can be easily fulfilled in a semi-quantitative way by PCR or Western blot analysis or in a quantitative way by real-time PCR [13,21,22] . Many of the CYPs that have been characterized to play major roles in xenobiotic or drug metabolism in the liver have also been identified in human skin.…”
Section: Discussionmentioning
confidence: 99%
“…In a later study, the real time PCR assays measured the CYP1-CYP4 mRNA levels in differentiating human epidermal keratino-cytes. Significant increases were found in CYP2C18 (113-fold), CYP2W1 (27-fold), and CYP4B1 (356-fold) by exposure to known CYP inducers and clinically relevant drug compounds [57].…”
Section: A) Rt-pcr and Real Time Pcrmentioning
confidence: 99%